An Empirical Research on the Perception of Job Seekers towards the Use of E-recruitment in Chennai - ROBERT. P, WILLIAM; REGINA.K (The journal of contemporary issues in business and government, 2020)
Human resource department (HRD) have undergone many changes in the present scenario.There are various innovations happening in HRD.The sourcing of candidates is transformed into e-recruitment. The study is aimed at understanding the perception of job seeker’s towards the effectiveness of E-recruitment. Descriptive research design was adopted as it explains the study and aims at finding the Perception of Job Seekers towards the Use of E-recruitment in Chennai. Primary data was collected from the 86 respondents by using Convenience sampling. The questionnaire is divided into various sections like demographic variables, independent variables includes attitude and dependent variables as intention to use. The collected data were classified tabulated and analyzed with statistical tools like frequency, mean analysis and Regression analysis. The results showed that the variables Comfort and Attitude are influencing the Intention to use.